(untitled) (The Review of Diabetic Studies, 2025)
Background: Primary​‍​‌‍​‍‌​‍​‌‍​‍‌ care nurses are the main drivers of the diabetes management education team. Yet, the relationship between nurses’ knowledge of nutrition and the self-management results of patients remains ambiguous in primary care settings. Objective: To find out the relationship between a primary care nurse’s knowledge of nutrition and the self-management quality of Type 2 Diabetes (T2D) patients. Method: Cross-sectional study of 187 nurses and their 1247 T2D patients from 12 primary care clinics. The nutritional knowledge of the nurses was measured by the validated Diabetes Nutrition Knowledge Test (DNKT, α=0.87). Patient self-management was measured by the standard Summary of Diabetes Self-Care Activities (SDSCA) scale. The interaction between nurse-level and patient-level variables was assessed by hierarchical linear modeling. Result: Nutritional knowledge of nurses was strongly associated with the quality of self-management of patients (r=0.512, p<0.001). Self-management of patients whose nurses scored ≥80% on DNKT was significantly better (M=42.3, SD=8.2) than that of patients whose nurses scored <60% (M=28.4, SD=10.1; p<0.001). Hierarchical linear modeling demonstrated that nurse nutritional knowledge accounted for 28% of the changes in patient self-management (β=0.512, p<0.001). The HbA1c level of patients guided by knowledgeable nurses through dietary counseling was better (7.2±1.1%) than that of patients taken care of by less knowledgeable nurses (8.4±1.3%, p<0.001). Conclusions: The knowledge level of primary care nurses about nutrition is a significant factor in predicting the quality of self-management of T2D patients. Healthcare facilities should utilize the nutritional competency of their nursing staff as a strategic resource in achieving better diabetes outcomes. The study findings support the continuous education program implementation and competency evaluation framework for diabetes nutrition knowledge.